Macacine alphaherpesvirus 1 (B Virus) Infection in Humans, Japan, 2019 - Yamada, Souichi; Katano, Harutaka; Sato, Yuko; Suzuki, Tadaki; Uda, Akihiko; Ishijima, Keita; Suzuki, Motoi; Yamada, Daigo; Harada, Shizuko; Kinoshita, Hitomi; Nguyen, Phu Hoang Anh; Ebihara, Hideki; et al. (Emerging infectious diseases, 2024)
Two human patients with Macacine alphaherpesvirus 1 infection were identified in Japan in 2019. Both patients had worked at the same company, which had a macaque facility. The rhesus-genotype B virus genome was detected in cerebrospinal fluid samples from both patients.